280 Male to Female Gender Reassignment Surgery; Developing Personalised Outcomes to Minimise Complications. (1st May 2022) - Attwell-Heap, A; Duncan, C
ABSTRACT: Introduction & Objectives: The Diagnostic and Statistical Manual of Mental Disorders has defined gender dysphoria as incongruence between gender identity and birth-assigned gender. Whilst the definition has been evolving in recent times, the first practice of Gender Reassignment surgery hates back to the mid-late 16 th century. Over time, more sophisticated techniques have developed to customise techniques to the individual to minimise post operative complications and ensure patient satisfaction. Methods: A review of the literature was performed on pubmed with key word searches; Gender Dysphoria, Gender Reassignment Surgery and history. Results: Gender affirming surgery was first described in the mid 16 th century, however precise documention of techniques was not seen until 1931 when the first gender affirming vaginoplasty was performed. Split skin grafts from the back, thigh or buttock were used for vaginoplasty, and less frequently, from intestines. It was Paul Fogh-Anderson in 1953 that widely publicised transformation on George Jorgensen in Denmark and popularised the penile skin graft neovagina. This technique of penile skin inversion was first used in Casablanca, Morocco in 1956. The intestinal vaginoplasty technique was described in the 1900s but not utilised in transgender vaginoplasty until 1974. Throughout the 80s, non genital skin flaps from the medial thigh were used. These multitude of techniques have meant that current practice goals are to construct a neopvagina individualised to patients needs. For patients wanting a functional rather than an asthetic, the neovagina should ideally be self-lubricating and with compliance allowing penetration. Currently, the recognised practices for creation of neovagina are penile inversion, skin grafts, local flaps and bowel vaginoplasty. As long term surgical outcome data for GRS is minimal, institutions should be encourage to gather long term data to aid in personalising the surgical approach to the individual patient. Conclusions: When counselling patients for Gender affirming surgery, it is important to understand the patients' needs to help minimise potential complications. Different surgical techniques of male to female GRS have been described and evolved over the 20 th century to the point of current best practice. Long term data will enable more personalisation and risk minimisation measures to ensure patient satisfaction. Disclosure: Work supported by industry: no.